The SV40 TC-II(kappa B) and the related H-2Kb enhansons exhibit different cell type specific and inducible proto-enhancer activities, but the SV40 core sequence and the AP-2 binding site have no enhanson properties. - Kanno, M (1989)
The enhancer activity of the oligomerized SV40 TC-I and TC-II sequences has been investigated in lymphoid and non-lymphoid cell lines. While the TC-I sequence had no demonstrable enhanson activity, a class C enhanson (proto-enhancer), 5'-GGAAAGTCCCC-3', overlapping the TC-II sequence and the GT-I enhanson was identified. This TC-II enhanson, which is identical to the kappa B motif from the kappa chain enhancer, was active in both lymphoid and non-lymphoid cells, which contrasts with the previously reported lymphoid cell specificity of the kappa B motif. However, its activity in non-lymphoid cells is in agreement with our previous reports describing the effect of mutations in the 'TC region' within the total SV40 enhancer in lymphoid and non-lymphoid cells. The activity of the TC-II enhanson could be moderately increased in HeLa by 12-O-tetradecanoyl-phorbol-13-acetate (TPA) and cycloheximide treatment, indicating that the protein(s) mediating its activity may be partially repressed by the previously described inhibitor protein I kappa B. The TC-II related, H-2Kb element, 5'-TGGGGATTCCCCA-3', of the histocompatibility class I H-2Kb gene promoter is also a class C enhanson which is active in both lymphoid and non-lymphoid cells. However, in contrast to the TC-II enhanson, the H-2Kb enhanson exhibits a very low activity in HeLa cells, but can be strongly induced by TPA and/or cycloheximide treatments which suggests that its cognate factor is inactivated (repressed) by an inhibitor protein. Interestingly, cycloheximide, but not TPA treatment, could induce the activity of both the TC-II and H-2Kb enhansons in F9 embryonal carcinoma cells, suggesting that these cells lack some component(s) of the protein kinase C signal transduction pathway. We also show that oligomers of the SV40 'core' sequence, which overlaps the TC-II enhanson, had no enhanson activity in any of the cell types studied, which questions the possible role of the AP-3 protein in SV40 enhancer activity in these cell types. In addition, oligomers of the AP-2 binding sites which are present in the SV40 TC region and in the human metallothionein IIA promoter show no enhanson activity, irrespective of whether the cells are treated with TPA.(ABSTRACT TRUNCATED AT 400 WORDS)